(untitled) (Journal of International Studies, 2020)
Contemporary newspaper reports and de-classified archival sources are used to revisit an infamous episode in the long, contentious, and very often violent encounter between colonial rule and the Muslim Moplah peasants. The significance of the Moplah rebellion is re-stated as being relevant and revelatory to all peoples, despite the timelessness of war, as it marks the emergence of protracted (asymmetrical) guerrilla tactics as the dominant mode of anti-colonial warfare. Moreover, the long series of suicide attacks by the Moplahs, and the punitive justice, summary executions, and abuse they experienced as prisoners at the hands of the colonial government, are all appallingly familiar today as part and parcel of ‘modern warfare’. Analysts, educators, policy makers and researchers are invited to review the events that constitute the Moplah rebellion (primarily as they were portrayed by newspaper reporters) in order to grasp the ‘new realities’ the conflict gave rise to, and to appreciate the wider international significance of what happened in Malabar (South India) at that time. Rather than speculate on the psychological and sociological facets of Moplah resistance and the politics of a mass movement, as in the case of the prevailing discourse on the Khilafat movement, new insight into the imbrications of the history of the Moplahs is provided by situating the events of the Moplah rebellion of 1921-22 against the contemporary background of militant Islamism and the on-going ‘War on Terror’.